2022
DOI: 10.1093/sleep/zsac114
|View full text |Cite
|
Sign up to set email alerts
|

Sleep architecture and regulation of male dusky antechinus, an Australian marsupial

Abstract: Study Objectives In this study, we (1) describe sleep behaviour and architecture, and (2) explore how sleep is regulated in dusky antechinus (Antechinus swainsonii), a small insectivorous marsupial. Our aim is to provide the first investigation into sleep homeostasis in a marsupial. Methods Wild-caught male dusky antechinus (n = 4) were individually housed in large indoor cages under a natural photoperiod of 10.5 h light / 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…A large proportion of the arguments set out for human versus rodent sleep scoring, whether it be manual or automated, are not only in need to be resolved for the sake of comparison between mammalian species but also to aid comparative research on sleep in non-mammalian species. With the technical advances of the last decades, sleep research has spread out over a large variety of mammalian and non-mammalian species (e.g., (Nath et al, 2017;Zaid et al, 2022)) and is more often examined in the wild, which comes with its own advances and limitations (Rattenborg et al, 2017). This expansion of model species for sleep has not only provided new light onto the evolution of sleep but has also shown that sleep is not easily divided into the same (sub)states in all species.…”
Section: Box: Other Animalsmentioning
confidence: 99%
“…A large proportion of the arguments set out for human versus rodent sleep scoring, whether it be manual or automated, are not only in need to be resolved for the sake of comparison between mammalian species but also to aid comparative research on sleep in non-mammalian species. With the technical advances of the last decades, sleep research has spread out over a large variety of mammalian and non-mammalian species (e.g., (Nath et al, 2017;Zaid et al, 2022)) and is more often examined in the wild, which comes with its own advances and limitations (Rattenborg et al, 2017). This expansion of model species for sleep has not only provided new light onto the evolution of sleep but has also shown that sleep is not easily divided into the same (sub)states in all species.…”
Section: Box: Other Animalsmentioning
confidence: 99%
“…Polygraphic correlates of SWS in marsupials closely resemble those of terrestrial placental mammals (Van Twyver and Allison, 1970 ; Zaid et al, 2022 ), despite variation in total sleep duration or SWS proportion between species (Siegel, 2005 ). Monotremes also show similar periods of quiet sleep with high-voltage EEG and reduced motor activity, for 6 to 8 h per day ( Figure 6A ) (Siegel et al, 1999 ; Siegel, 2022 ).…”
Section: Temporal Organisation Of Cortical Activitymentioning
confidence: 92%
“…For each species, the EEGs in the three states of alertness are presented on the same scale. Data are adapted from Siegel et al ( 1999 ) (platypus); Zaid et al ( 2022 ) (dusky antechinus); Mahon et al ( 2006 ) (rat); Stickgold and Walker ( 2010 ), Liu and Dan ( 2019 ) (human). (B) Bilateral EEG recordings (L: left, R: right) from a semi-aquatic northern fur seal during SWS, showing bilateral high-voltage slow waves when animals are sleeping on land (BSWS, top) and unihemispehric slow-wave activity when sleeping in the sea (USWS, bottom).…”
Section: Temporal Organisation Of Cortical Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…While we appreciate the ethical questions and logistical challenges of recording EEG signals through the 30 cm-thick cranium of adult elephants, the use of trunk immobility as a proxy for sleep is unverified (as noted by Gravett and colleagues [ 21 ]). As such, the elephants may have fallen asleep rapidly between trunk movements, much in the way that dusky antechinus ( Antechinus swainsonii ) (a small marsupial mammal) falls asleep quickly once immobile and has hundreds of sleep bouts per day, each mere tens of seconds long [ 26 ]. Furthermore, the elephants could have spent considerable amounts of time ‘drowsy’.…”
Section: Elephant Matriarchsmentioning
confidence: 99%